The Unseizable Landscape of the Real: The Poetry and Poetics of Philippe Jaccottet - Richard Stamelman (Studies in 20th & 21st Century Literature, 1989)
For Philippe Jaccottet the real is the force of life itself. It is also a rapid, fleeting perception made all the more ephemeral by the mimetic imprecision of language. The essence of the real, since it is always other than what is said about it, can never be fully represented. This alterity of the real and the fundamental lack it announces provoke poetic language. By means of a poetics of passage, of passing through, of a travers, Jaccottet confronts the otherness of the unseizable landscape and of the elusive language in which he dwells. In the meditative, prose poem A Travers un verger (1975) he traverses the mysterious space of an orchard and a text, of trembling blossoms and quivering words, in an effort to understand the opposition between the limits of language and the limitlessness of the real. Out of the experience of landscape and the language that describes it—out of the epiphany of the real that a flowering orchard sustains but that images only fail to seize—"something" is perceived: an ineffable, indescribable "something" that dwells in the beyond of representation.
Keywords: Philippe Jaccottet; force; perception; ephemeral; essence; real; fundamental; poetic language; travers; unseizable landscape; meditative; prose; poem; A Travers un verger; space; orchard; language; epiphany; something; ineffable; indescribable; beyond; representation